Exploring the Photophysics of Cinnamoyl-Coumarin Derivatives in Cucurbit [7]Uril Complexes and Assessing Phototoxicity in Hela Cells - Aspee-Lamas, A; Zúñiga-Núñez, D; Mura-Mardones, F (Elsevier Ltd, 2024)
Cinnamoyl-coumarin derivatives containing 5 or 12 carbon aliphatic chains were evaluated as photosensitizers and their photophysical properties were studied in detail. Moreover, these compounds were encapsulated in cucurbit[7]uril macrocycle with relatively high binding affinities in aqueous media. Fluorescence quantum yields, fluorescence lifetimes and singlet oxygen quantum yields were measured upon encapsulation. Computational DFT calculations and molecular dynamics simulations allowed the visualization of the binding modes of both derivatives inside the macrocycle. In particular, the free energy profiles for the insertion of the molecules into the macrocycle were determined to assess the most probable conformations of the complexes in water. In vitro phototoxicity assays were carried out in HeLa cells showed significant decreases in cell viability upon illumination of the 5 carbon aliphatic chain derivative at 460 nm with an LED source at different concentrations and enhanced by cucurbit[7]uril. However, the one with 12 carbon aliphatic chain did not display any phototoxicity regardless of the presence of cucurbit[7]uril. This behavior is related to the high lipophilicity introduced by a 12 carbon aliphatic chain conditioning its distribution on hydrophobic compartments and decreasing its phototoxicity. The enhanced phototoxicity elicited by cucurbit[7]uril on the 5 carbon aliphatic chain derivative but not in the 12 carbon derivative remark that there is a balance between hydrophobicity of these probes with the carrier properties of cucurbit[7]uril to be reach for effective phototoxicity properties. © 2024